The Challenges, Trends, and Strategies of Education Learning Technique in Higher Education for the Post COVID-19 - Mohammad Sofwan Effendi; Phimlikid Kaewhanam; Syifa Izdihar Firdausa Asfianur (Universitas Negeri Malang, 2023)
The COVID-19 pandemic has resulted from the government management policy in higher education to provide distance learning. This study analyzes the development trend of educational management research publications in e-learning education. The research involved qualitative methods with bibliometric analysis—the data source from the article database in Scopus from 2019-2022. Two points are obtained as the result of this study. First, based on territory, the authors who wrote the most publications on education management in universities during COVID-19 were Aleshkovski, I.A. Gasparishvili, A.T. Krukhmaleva, O.V., reaching 3.5. As a result, with the criteria for the most published territories about education management during the COVID-19 pandemic, the United States occupied 43 publications and received the highest search rating from 2019 to 2022. Second, learning management strategies could be provided by elaborating on e-learning as a teaching tool, integrating e-learning into teaching and learning strategies, working on a pre-strategy, and the executive decision to top-down investments in the information and technology infrastructure. Keywords: The COVID-19 pandemic, Education, Management strategy, Higher education, Learning technique